Processing of prosodic cues of uncertainty in autistic and non-autistic adults: a study based on articulatory speech synthesis - Bellinghausen, Charlotte; Schröder, Bernhard; Rauh, Reinhold; Riedel, Andreas; Dahmen, Paula; Birkholz, Peter; Tebartz van Elst, Ludger; Fangmeier, Thomas (Frontiers in Psychiatry, 2024)
Introduction We investigated the prosodic perception of uncertainty cues in adults with Autism Spectrum Disorder (ASD) compared to neurotypical adults (NTC). Method We used articulatory synthetic speech to express uncertainty in a human-machine scenario by varying the three acoustic cues pause, intonation, and hesitation. Twenty-eight adults with ASD and 28 NTC adults rated each answer for uncertainty, naturalness, and comprehensibility. Results Both groups reliably perceived different levels of uncertainty. Stimuli were rated as less uncertain by the ASD group, but not significantly. Only when we pooled the recipients’ ratings for all three cues, did we find a significant group difference. In terms of reaction time, we observed longer reaction times in the ASD group compared to the neurotypical comparison group for the uncertainty level hesitation & strong intonation, but the differences were not significant after Bonferroni correction. Furthermore, our results showed a significant group difference between the correlation of uncertainty and naturalness, i.e. the correlation in the ASD group is significantly lower than in the NTC group. Obtained effect size estimates can inform sample size calculations in future studies for the reliable identification of group differences. Discussion In future work, we would like to further investigate the interaction of all three cues and uncertainty perception. It would be interesting to further vary the duration of the pause and also to use different types of fillers. From a developmental perspective, uncertainty perception should also be investigated in children and adolescents with ASD.